2016
DOI: 10.1016/j.jvb.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between career adaptability and job content plateau: The mediating roles of fit perceptions

Abstract: This study is the first to test career adaptability as an antecedent of the job content plateau. Based on career construction theory and person-environment fit theory, it examined the mediating effects of person-job fit and person-organization fit on the relationship between career adaptability and the job content plateau. Results from 270 full time workers showed that employees with higher levels of career adaptability were less likely to experience job content plateaus. Partial mediating effects were found f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 52 publications
8
76
0
1
Order By: Relevance
“…Career plateau. Hierarchical plateau and job content plateau were measured using Milliman's (1992) career plateau scales, which are the measures typically used in contemporary career plateau studies (Jiang, 2016;Wang et al, 2014). Both types of plateau were measured using six items, on a 5-point agreement scale (1 = strongly disagree, 5 = strongly agree).…”
Section: Methodsmentioning
confidence: 99%
“…Career plateau. Hierarchical plateau and job content plateau were measured using Milliman's (1992) career plateau scales, which are the measures typically used in contemporary career plateau studies (Jiang, 2016;Wang et al, 2014). Both types of plateau were measured using six items, on a 5-point agreement scale (1 = strongly disagree, 5 = strongly agree).…”
Section: Methodsmentioning
confidence: 99%
“…Lemire et al (1999) further found work perseverance to be negatively related to hierarchal plateau. Additionally, recent studies by Jiang (2016) and Jiang, Hu, and Wang (2018) showed career adaptability to be negatively associated with job content plateau, suggesting that individuals who consciously adjust themselves to the work conditions through self-regulation are less likely to perceive stagnation in job challenge.…”
Section: Antecedents Of Career Plateaumentioning
confidence: 98%
“…For example, longitude data could be used to explore the relationship between trust and control. Also, the single source data tend to bring about common method biases [96,97]. Moreover, some control variables were not considered in this research, such as the competence of the contractor and the attitude or propensity of the owner.…”
Section: Discussionmentioning
confidence: 99%